Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1097/mnm.0b013e32835e6ac6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of 18F-dihydroxyphenylalanine positron emission tomography in patients with congenital hyperinsulinism

Abstract: In patients with CHI, F-DOPA PET or PET/CT demonstrated high sensitivity and specificity. F-DOPA PET and PET/CT are accurate methods for the diagnosis of CHI. Nevertheless, possible sources of false-positive and false-negative results should be kept in mind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
3
17
0
1
Order By: Relevance
“…An I 2 statistic was also analyzed to test for heterogeneity between studies [15]. The statistical analysis of this meta-analysis referred to a previous meta-analysis [16][17][18][19]. Statistical analyses were performed using Meta-DiSc statistical software, version 1.4 (Unit of Clinical Biostatistics, Ramony Cajal Hospital, Madrid, Spain) [20].…”
Section: Discussionmentioning
confidence: 99%
“…An I 2 statistic was also analyzed to test for heterogeneity between studies [15]. The statistical analysis of this meta-analysis referred to a previous meta-analysis [16][17][18][19]. Statistical analyses were performed using Meta-DiSc statistical software, version 1.4 (Unit of Clinical Biostatistics, Ramony Cajal Hospital, Madrid, Spain) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Following the initial description of its role in identifying the focal lesion38), its usefulness has been reported in a number of publications39,40). 18 F-DOPA PET detects focal lesions as small as 5 mm and is better preformed as PET-CT.…”
Section: Known Etiologies Of Chi (Table 2)mentioning
confidence: 99%
“…In diffuse CHI there is generalised increased tracer uptake with a relatively higher uptake in the head when compared to the rest of the pancreas [14,26,27] . 18 F-DOPA is excreted by kidneys hence normal bio-distribution is seen in kidneys, ureter and urinary bladder.…”
Section: +mentioning
confidence: 99%
“…The area under the summary receiver operating characteristic curve (SROC) was estimated to be 0.92% suggesting that 18 F-DOPA PET and PET/CT imaging are accurate tools for distinguishing focal diagnosing CHI, although there is a minimal risk of both false positive and false negative results. The authors concluded that 18 F-DOPA PET is very helpful in differentiating between focal and diffuse lesions, and should be the first investigation of choice when the genetic test results are inconclusive and 18 F-DOPA PET/CT is very helpful in localising the lesion and thereby improving the treatment outcome in focal CHI [27] . Blomberg et al [38] conducted a systematic review and meta-analysis recently to quantify the diagnostic performance of pancreatic venous sampling (PVS), selective pancreatic arterial calcium stimulation with hepatic venous sampling (ASVS) and 18 F-DOPA-PET/CT in diagnosing and localising focal CH.…”
Section: F-dopa-pet/ct In Chimentioning
confidence: 99%